Thematisierte Selbstzensur deutscher Autoren vor und nach 1945 - Michalak-Etzold, Magdalena (Studia Germanica Posnaniensia, 2018)
The increasing institutional censorship in National-Socialist Germany forced authors to control carefully those thoughts wich were to be published. This process of self-censorship is analyzed in the following, focusing on the reflections of these authors concerned. Referring to the posthumous works of Werner Bergengruen, Elisabeth Langgässer, Oskar Loerke, Ina Seidel und Willy Vesper the essay is representing the view that the authors generally could not evade internal censorship and could hardly free themselves of it, even after the institutional censorship system had collapsed. The following essay is based on research conducted at the ,,Deutsches Literaturarchiv" in Marbach (Germany).